NEW DEVELOPMENTS IN HADITH STUDIES: ESTABLISHING THE FOUNDATIONS OF HADITH STUDIES ON DIGITAL PLATFORMS - Al Anwari, Ahmad Ubaidillah Ma'sum; Al Fatach, M. Khabib (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
This article discusses the ongoing digital transformation, which not only affects people’s lifestyles but also influences the field of Islamic studies. The emergence of various digital platforms providing hadiths has, on the one hand, made access easier and saved time for users. Hadith books are no longer limited to printed form but are now available in PDF and app formats. However, on the other hand, new challenges related to the authenticity of hadith and the validity of their meanings are also at stake. This study aims to examine the transformation, opportunities, challenges, and academic efforts in establishing verification standards and raising awareness among the public who use digital platforms as a medium for reading, analyzing, understanding, and disseminating hadith. Using a descriptive-analytical literature review method, the research findings highlight the urgent need to consistently adhere to the principles of hadith science established by classical scholars. Their presence is a crucial prerequisite for the broader public who use digital platforms as a medium for seeking, reading, understanding, and disseminating hadith to a wider audience. Additionally, carefulness and caution are required in selecting verified digital platforms to avoid technical errors during the review process, making this balance crucial while leveraging the transformative potential of digital technology.